Ventral Visual Pathway-Cerebellar Circuit Deficits in Alcohol Dependence: Long- and Short-Range Functional Connectivity Density Study - Chen, Lingling; Liu, Bi-Xia; Liu, Run; Zheng, Jiyong; Dai, Xi-Jian (Frontiers in Neurology, 2019)
Objective: To identify the underlying intrinsic functional connectome changes in patients with alcohol dependence. Methods: Functional connectivity density (FCD) analysis was used to report on the functional connectivity changes in 24 male patients with alcohol dependence (age, 47.83 ± 6.93 years) and 24 male healthy subjects (age, 47.67 ± 6.99 years). We defined the voxels with a correlation threshold of r > 0.25 inside their neighborhood (radius sphere ≤ 6 mm) as shortFCD, and radius sphere > 6 mm as longFCD. We repeated the network analysis using a range of correlation r thresholds (r = 0.30, 0.35, 0.40, 0.45, 0.50, 0.6, and 0.75) to determine whether between-group differences were substantially affected by the selection of different r-value thresholds used. ROC curve was used to test the ability of the FCD in discriminating the two groups. Pearson correlation was used to to evaluate the relationships between the FCD differences in brain areas and demographic characteristics. Results: The covered differences in brain areas in binarized shortFCD were larger than binarized longFCD in both groups. The intra-group FCD differences did not depend on the selection of different threshold used. Patients with alcohol dependence was associated with the longFCD deficit in the cerebellum posterior lobe, and shortFCD deficit in the ventral system of visual pathway and increased shortFCD in the left precentral gyrus, right salience network and right cingulate gyrus. ROC curve demonstrated that these specific brain areas alone discriminated the two groups with high degree of sensitivities and specificities. In the alcohol dependence group, the cerebellum posterior lobe, visual association cortex and salience network displayed significant correlations with demographic characteristics. Conclusions: The shortFCD analysis is more sensitive than the longFCD analysis to find the differences in brain areas. The ventral visual pathway-cerebellar circuit deficit appears to be disturbed in patients with alcohol dependence.